2021
DOI: 10.1021/acs.jpcb.1c00488
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stages of Spontaneous Binding of Folate-Based Vectors to Folate Receptor-α Observed by Unbiased Molecular Dynamics

Abstract: Active targeting is a prospective strategy for controlled drug delivery to malignant tumor tissues. One of the approaches relies on recognition of a bioactive ligand by a receptor expressed abundantly on the surface of cancer cell membranes. A promising ligand−receptor pair is folic acid (or its dianionic form, folate) combined with the folate receptor-α (FRα). A number of targeting drug delivery systems based on folate have been suggested, but the mechanism of binding of the ligand or its derivatives to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Moreover, Della-Longa and Arcovito set up metadynamics calculations and reported a free energy barrier for the FA escape from FRα of 18 kcal mol –1 . Schaber et al, using unbiased classical MD instead, demonstrated that FA binding occurs spontaneously on the nanosecond time scale, without applying any bias to the system …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Della-Longa and Arcovito set up metadynamics calculations and reported a free energy barrier for the FA escape from FRα of 18 kcal mol –1 . Schaber et al, using unbiased classical MD instead, demonstrated that FA binding occurs spontaneously on the nanosecond time scale, without applying any bias to the system …”
Section: Introductionmentioning
confidence: 99%
“…14 Schaber et al, using unbiased classical MD instead, demonstrated that FA binding occurs spontaneously on the nanosecond time scale, without applying any bias to the system. 15 Certainly, the striking interaction between FA and the FR can be exploited to design effective nanomedical devices for drug release or tumor imaging, which upon FA functionalization can be selectively driven toward FRα-expressing tumor cells. This allows to obtain a targeted therapy with limited side effects related to unwanted delivery of cargos at normal cells.…”
Section: Introductionmentioning
confidence: 99%